A concise approach to indoles via oxidative C–H amination of 2-alkenylanilines using dioxygen as the sole oxidant. Issue 42 (13th April 2016) - Ma, Ai-Lun; Li, Yin-Long; Li, Jian; Deng, Jun
Abstract : An operationally simple and environmental friendly approach to indole derivatives from N -Ts-2-alkenylanilines has been achieved, which involves an oxidative intramolecular C–H amination by using molecular oxygen as sole oxidant. Abstract : A novel synthetic method to prepare indole derivatives from N -Ts-2-alkenylanilines has been achieved. This reaction is through an oxidative intramolecular C–H amination by using molecular oxygen as the sole oxidant. This protocol is operationally simple and environmental friendly, and provides a diverse range of substrate scope.